Gestalt Prototyping Framework applied to design a Mobile-Commerce interface - Ripalda, Daniel (2021)
This article presents the different concepts that were considered to design the interface of an e-commerce platform and its consequent adaptation to a mobile environment. The parameters considered during the development of the high and low fidelity prototypes are the result of an association between usability heuristics, Gestalt principles, and specific user experience (UX) interactions. This project shows the results of the projections of the usability tests carried out on the functional application, in which it was possible to understand the close relationship between the use of usability concepts that intervene in the functional actions of the application with the perception of aesthetics.